2010
DOI: 10.1073/pnas.1006899108
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of SNARE-driven membrane fusion and neuroexocytosis by wedging small hydrophobic molecules into the SNARE zipper

Abstract: Neuronal SNARE proteins mediate neurotransmitter release at the synapse by facilitating the fusion of vesicles to the presynaptic plasma membrane. Cognate v-SNAREs and t-SNAREs from the vesicle and the plasma membrane, respectively, zip up and bring about the apposition of two membranes attached at the Cterminal ends. Here, we demonstrate that SNARE zippering can be modulated in the midways by wedging with small hydrophobic molecules. Myricetin, which intercalated into the hydrophobic inner core near the middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(89 citation statements)
references
References 36 publications
6
81
2
Order By: Relevance
“…Generally, the effect of extracts on SNARE-driven membrane fusion was abolished when the colors were removed. It is likely that polyphenols are associated with the activity as we have demonstrated that some polyphenolic compounds wedge into SNARE complex and stop neuroexocytosis (Yang et al, 2010). Intriguingly, however, Potentilla chinensis extract did not exhibit such a strong color or order, and could be dissolved well in water as high as 300 mg/L which is 30 times higher concentration than those that inhibited approximately 90% neuroexocytosis ( Figure 3A).…”
Section: Muscle Paralysis Using Rat Phrenic Nerve-hemidiaphragmmentioning
confidence: 92%
See 4 more Smart Citations
“…Generally, the effect of extracts on SNARE-driven membrane fusion was abolished when the colors were removed. It is likely that polyphenols are associated with the activity as we have demonstrated that some polyphenolic compounds wedge into SNARE complex and stop neuroexocytosis (Yang et al, 2010). Intriguingly, however, Potentilla chinensis extract did not exhibit such a strong color or order, and could be dissolved well in water as high as 300 mg/L which is 30 times higher concentration than those that inhibited approximately 90% neuroexocytosis ( Figure 3A).…”
Section: Muscle Paralysis Using Rat Phrenic Nerve-hemidiaphragmmentioning
confidence: 92%
“…We added 1% n-octyl-d-glucopyranoside (OG) to syntaxin 1a and VAMP2. The purified proteins were examined by 12.5% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), and the purity was at least 90% for all proteins ( Figure 1B) (Jung et al, 2008;Yang et al, 2010).…”
Section: Expression and Purification Of Recombinant Protein Preparationmentioning
confidence: 99%
See 3 more Smart Citations